The Palgrave Handbook of Disability Sport in Europe Policies, Structures and Participation - van Lindert, Caroline; Scheerder, Jeroen; Brittain, Ian. (Cham : Springer International Publishing : Imprint: Palgrave Macmillan, 2023)
"This volume is likely to fill a large gap in the market and is set to become the 'go to' text on sports participation among people with disabilities. The book is very well structured around a similar organising principle which eases the task of reading and comparing between the multiple European case studies presented." - Jonathan Grix, Professor of Sport Policy and Politics, Manchester Metropolitan University, UK "This handbook will make an important contribution by enabling the development and exchange of knowledge in the areas of sport participation and policies and inclusion of persons experiencing disability among practitioners, policy makers and researchers." - David Legg, Professor at the Department of Health and Physical Education, Mount Royal University, Calgary, Canada, and President of the International Federation of Adapted Physical Activity This handbook explores the various ways in which disability sport is governed and organised across Europe, as well as examining the extent to which persons with a disability participate in sport at the grassroots level. Based upon a solid theoretical framework and up-to-date data, the 19 country-specific chapters in this handbook give a comparative overview of the structuring, steering and supporting elements of disability sport policy and sport participation levels amongst persons with a disability, as well as the extent to which countries adopt policies to promote inclusion in sport in this population. A multitude of authors also identify the various methods and challenges in collecting sport participation data with regard to persons with a disability. This handbook will be a valuable resource for academic study across a range of sport and disability related programs, as well as a point of reference for researchers and policymakers working in this area. Caroline van Lindert is Senior Researcher at the Mulier Institute, Utrecht, The Netherlands. Jeroen Scheerder is Professor in the Faculty of Movement & Rehabilitation Sciences, KU Leuven, Belgium, and head of the Policy in Sports & Physical Activity Research Group. Ian Brittain is Associate Professor (Research) in the Centre for Business in Society at Coventry University, UK.
1. Introduction. Sport participation a human right for persons with a disability -- 2. Understanding disability, disability sport and inclusion -- 3. Participation in sport and physical activity amongst people with a disability. A pan-European comparative approach -- 4. Denmark: Disability sports policy at arm's length -- 5. Finland. Facts behind the long and complicated process of disability inclusion in sports -- 6. Disability and sport in Iceland -- 7. Norway -- 8. Beyond inclusion - opportunity structures in sports for all in Sweden -- 9. Ireland -- 10. Northern Ireland: Disability Sport in a Shared Space -- 11. United Kingdom: An inclusionary approach to sport -- 12. Austria: Half Way to Inclusion? -- 13. Disability sport in Belgium/Flanders. From a fragmented mosaic towards a more inclusive landscape -- 14. Complexity and Coexistence: Disability Sport in Germany -- 15. The Netherlands, towards inclusive sport for people with a disability -- 16. Switzerland -- 17. Hungary: Rise of attention given to disability sports -- 18. Disability Sport in Lithuania -- 19. Structure of the analysis on the development and situation of disability sport in Slovenia -- 20. Portugal: pathways of sport for people with disabilities -- 21. Disability sport in Spain -- 22. Turkey (Republic of Turkey): Disability Sports, Policies and Implementations -- 23. The landscape of sport for persons with a disability: a system within a system.
Keywords: Sports -- Sociological aspects; Social policy; Sports sciences; Sport Sociology; Social Policy; Sport Science